Assessment of knowledge and practice of breast self-examination among reproductive age women in Akatsi South district of Volta region of Ghana. - Rita Dadzi; Awolu Adam (PLoS ONE)
Background Breast cancer is the primary cause of cancer death among women globally, responsible for about 425,000 deaths in 2010. This study assessed the awareness, knowledge and practices of breast self-examination as a method of prevention and early diagnosis of breast cancer among reproductive aged women in Akatsi South district in Volta region of Ghana. Methods This study was a cross-sectional study involving 385 women between the ages of 15-49 years. Data were collected with a structured questionnaire and variables included socio-demographic characteristics, breast cancer knowledge, breast self-examination knowledge and practice. Descriptive statistics were used to analyze and present the data and chi square test of significance was used to determine association between socio-demographic variable and practice of breast self-examination. Results The mean age of the women was 24.54±7.19. Only 3.1% of women had no formal education and 58.9% were single. Although 88.3% of the respondents were aware of breast cancer, 64.9% of the respondents had good or sufficient knowledge of breast cancer and only 94(37.6%) practice BSE. Over 50% of the respondents did not know how to perform BSE. There was a significant association between knowledge on breast cancer and practice of BSE (χ2 = 36.218 p = 0.000). The higher the age of a participant, the lower practice of breast self-examination and this was significant (χ2 = 11.324, p = 0.003). Conclusion Breast self-examination is a key strategy to early detection of breast cancer and subsequently critical for effective treatment and cure of the disease. The findings in this study have shown significant low levels of awareness and practice of breast self-examination among women in Akatsi South district of the Volta region. This pattern may be similar to other rural communities across the region. The need to create awareness and to educate women, especially rural women, on importance of breast self-examination as preventive measure for breast cancer is paramount.